Assessing the Work Results of Vietnamese Civil Servants - Trung, Ngo Sy; Loan, Nguyen Thi To (Journal of Ecohumanism, 2024)
Commune-level public servants work as implementers of state policies and laws to ensure the legitimate rights and interests of the people; hence, their work results are significant to affirm the effectiveness and reputation of state agencies. In terms of theory and practice, their work results are shown in the progress and quality of implementing assigned tasks; affected by both subjective factors (qualifications, capacity, working attitude, etc. of public servants), objective factors (working environment, facilities, technology, etc. of state agencies). This study focuses on two subjective factors that have direct impacts on the work results of civil servants, including: Professional capacity and working capacity. A survey was conducted with 330 leaders of commune-level authorities in 3 provinces representing 3 regions of Vietnam: Thai Binh province (Northern region), Ha Tinh province (Central region), Bac Lieu province (Southern region). The results show that: Commune-level public servants’ professional qualifications meet rank standards and job position requirements; however, they are not highly evaluated for their practical working capacity from their managers. The findings suggest policy development to promote the professional practical working capacity of public servants to accomplish the public service.